POSISI SISTEM INFORMASI SEBAGAI AKTIVA DAN BIAYA PADA PELAPORAN KEUANGAN - Mujilan, Agustinus (Widya Warta, 2009)
Information system plays a crucial role in organizations or companies. It provides information needed by organizations and managements to support the decision making. Information  system  is actually as important  as other resources such  as  manpowers,  or raw materials. Some activities involved within information system are systems analysis and design, implementation, maintenance, safeguarding, etc. This study aimed to observe the financial reports, especially those of the companies listed in the Indonesia Stock Exchange. This work tried to investigate whether or not the companies classified and presented information system in their financial reports. It focused on the analysis of the positions of assets, costs, and expenses. The result of this survey showed that most of the companies didn’t explicitly write the information system on the balance sheet or in the lost and profit reports. But, some companies wrote it in the explanation of the financial report.